Suki's kimono - Uegaki, Chieri (Kids Can Press, 2003)
Suki's favorite possession is her blue cotton kimono. A gift from her obachan, it holds special memories of her grandmother's visit last summer. And Suki is going to wear it on her first day back to school --- no matter what anyone says. When it's Suki's turn to share with her classmates what she did during the summer, she tells them about the street festival she attended with her obachan and the circle dance that they took part in. In fact, she gets so carried away reminiscing that she's soon humming the music and dancing away, much to the delight of her entire class! Filled with gentle enthusiasm and a touch of whimsy, Suki's Kimono is the joyful story of a little girl whose spirit leads her to march --- and dance --- to her own drumbeat.